2015
DOI: 10.1111/ocr.12101
|View full text |Cite
|
Sign up to set email alerts
|

Growth characteristics underlying the lack of a chin in pigs: a histomorphometric study

Abstract: Objectives Despite similar mandibular growth to that of humans, pigs lack a chin projection as shown in most humans. To understand whether this divergence is contributed to differences in local symphyseal growth, this project characterized bone modeling activities at the symphyseal surfaces of juvenile pigs. Material and Methods Symphyseal specimens from 2 age groups (4- and 6-month-old, n=10) were processed into histological sections with and without decalcification, which were assessed for surface mineral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…To determine mandibular locations possible for direct bone marrow aspiration, computed tomography (CT) images and histological sections of 6 pigs from a previous independent study (IACUC protocol 2008A0080) were observed (Price et al, 2015). The inferior third of the symphysis, characterized by well-corticated labial and lingual plates housing a large quantity of trabecular bones in between, present a likely source for direct bone aspiration (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…To determine mandibular locations possible for direct bone marrow aspiration, computed tomography (CT) images and histological sections of 6 pigs from a previous independent study (IACUC protocol 2008A0080) were observed (Price et al, 2015). The inferior third of the symphysis, characterized by well-corticated labial and lingual plates housing a large quantity of trabecular bones in between, present a likely source for direct bone aspiration (Fig.…”
Section: Methodsmentioning
confidence: 99%